2014
DOI: 10.1007/s00392-014-0754-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of aldosterone antagonists for preventing atrial fibrillation after cardiac surgery in patients with systolic heart failure: a retrospective study

Abstract: Postoperative atrial fibrillation (POAF) is the most common arrhythmia after cardiac surgery. There exist consistent experimental and clinical data suggesting that aldosterone antagonists (AAs) may exert beneficial effects regarding electrical and structural remodeling in failing myocardium. Recently, eplerenone (EPL) has been found to reduce the incidence of nonsurgical AF when added to guideline-recommended therapy in patients with systolic heart failure. Based on these findings, we primarily aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Eplerenone has also been reported to reduce the incidence of new-onset AF in a subanalysis of the Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure (EMPHASIS-HF) trial [25]. The most recent study showed that aldosterone antagonists, both eplerenone and spironolactone, exert beneficial effects for preventing AF after cardiac surgery in patients with systolic heart failure [26]. The incidence and prevalence of AF in ESRD patients are higher than that in general population and are associated with increased risks of stroke and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Eplerenone has also been reported to reduce the incidence of new-onset AF in a subanalysis of the Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure (EMPHASIS-HF) trial [25]. The most recent study showed that aldosterone antagonists, both eplerenone and spironolactone, exert beneficial effects for preventing AF after cardiac surgery in patients with systolic heart failure [26]. The incidence and prevalence of AF in ESRD patients are higher than that in general population and are associated with increased risks of stroke and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with reduced LVEF are at increased risk of developing AF . Therefore, long‐term outcomes after successful catheter ablation of AF may be worse in this patient population .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Patients with reduced LVEF are at increased risk of developing AF. 9 Therefore, long-term outcomes after successful catheter ablation of AF may be worse in this patient population. 10 Long-term results after catheter ablation of AF in patients with reduced systolic LVEF are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The doses used were below those required to lower blood pressure or have a diuretic effect. As predicted from animal studies, some done more than 50 years earlier 60, 97 , spironolactone and eplerenone were shown to decrease cardiac arrhythmias in patients through direct effects on cardiomyocyte excitation, as well as by decreasing sympathetic nervous system activation and normalizing hypokalemia and hypomagnesaemia, including in those with coronary artery disease and chronic kidney disease without heart failure 96, 98103 .…”
Section: The First Generation Antagonistsmentioning
confidence: 84%